Stresses and displacements for shallow foundations - Milovic, D. (Developments in geotechnical engineering, 1992)
This monograph presents the results of the theoretical analyses of stresses and displacements for shallow foundations subjected to various types of loads. In these analyses not only the classical models but more complex models of soils have been used, such as two-layer half-space, homogenous compressible layer of finite thickness, two-layer compressible layer of finite thickness, anisotropic compressible layer. Contact stresses, settlements, vertical stress distribution, bending moments and shear forces have been determined for foundations of any rigidity. Numerous values of the dimensionless coefficients "I" are tabulated, which can be of use in the solution of practical engineering problems